EPA configurations : the Caribbean countries : the EC-CARIFORUM EPA (European Commission [Brussels]BE, 2008)
Looks briefly at the chapter on agriculture in the agreement and also highlights three declarations concerning agricultural products viz. rice, bananas and sugar.
Keywords: PARTNERSHIP